EFFECT OF MOZART CLASSICAL MUSIC THERAPY ON PAIN INTENSITY REDUCTION IN POST-OPERATIVE FRACTURE PATIENTS AT CENDANA 3, RSUP DR. SARDJITO - Rahmawati, Umi; Purwaningsih, Iswanti (Medical-Surgical Journal of Nursing Research, 2024)
The pain felt by the patient if not treated will hinder the fulfillment of daily needs and prolong the period of treatment in the hospital. To get an overview of classical Mozzart musik therapy to reduce pain intensity in postoperative fracture patients.This scientific paper research method uses a descriptive case study with one patient subject according to the inclusion criteria. With the NRS observation sheet assessment instrument. Based on research conducted on the first day the highest scale before treatment was 6 with NRS and the lowest scale after therapy was 2. On the second day, the highest scale before therapy was 4 and the lowest scale after therapy was 1, and the second day The third highest scale before therapy is 1 and the lowest scale after therapy is 0. There is an effect of classical Mozzart musik therapy on reducing pain intensity in postoperative fracture patients.